1924
DOI: 10.1098/rspb.1924.0037
|View full text |Cite
|
Sign up to set email alerts
|

Muscular exercise, lactic acid, and the supply and utilisation of oxygen.—Parts ӏ-ӏӏӏ

Abstract: In a recent paper under the general title of this series A. V. Hill and Lupton (1) gave a preliminary account of experiments made on man, in an attempt to press to its logical conclusion the physico-chemical view of muscular contraction arrived at by the investigation of the isolated muscle. The present series of papers contains a more adequate account of these experiments, which are still in progress. ( a ) The “ Initial ” Process . In the isolated muscle the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
3
3

Year Published

1927
1927
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(52 citation statements)
references
References 30 publications
(15 reference statements)
2
43
3
3
Order By: Relevance
“…They also are consistent with the effects of inspired hypoxia (1,11,19,25,29,38) and hyperoxia (1,11,19,38) on decreasing and increasing performance, respectively. Because we also found that the magnitude of locomotor muscle fatigue was attenuated by preventing EIAH and exacerbated by increasing arterial hypoxemia, does this mean that locomotor muscle fatigue caused the changes in performance?…”
Section: Eiah Fatigue and Exercise Performance Limitationssupporting
confidence: 74%
See 1 more Smart Citation
“…They also are consistent with the effects of inspired hypoxia (1,11,19,25,29,38) and hyperoxia (1,11,19,38) on decreasing and increasing performance, respectively. Because we also found that the magnitude of locomotor muscle fatigue was attenuated by preventing EIAH and exacerbated by increasing arterial hypoxemia, does this mean that locomotor muscle fatigue caused the changes in performance?…”
Section: Eiah Fatigue and Exercise Performance Limitationssupporting
confidence: 74%
“…This finding was interpreted to reflect an increase in motor unit recruitment to compensate for the fatigue (47). In contrast, it has been argued that systemic hypoxemia may reflexively inhibit central motor output to locomotor muscles to ensure that a catastrophic failure of homeostasis does not occur during exercise (3,19). This proposal is supported by the finding that cycle exercise during chronic severe hypoxia is terminated without evidence of peripheral muscle fatigue, again as inferred by the absence of hypoxic effects on limb muscle EMG activity (26).…”
mentioning
confidence: 99%
“…The second important property of the V O 2 Ápower output relationship is that there is an upper limit to the increase in V O 2 (V O 2max ). The concept of V O 2max was originally established using discontinuous constant-load exercise testing (Å strand & Saltin, 1961a;Hill & Lupton, 1923), but it is well known that the peak V O 2 observed in the more common ramp test is identical to V O 2max measured using constant power output exercise ( Figure 1C; see also Day, Rossiter, Coats, Skasick, & Whipp, 2003).…”
Section: Oxygen Uptake Response To Exercise: Traditional Conceptsmentioning
confidence: 99%
“…Since the work of Krogh and Lindhard (1920) and Hill and Lupton (1923), it has been widely appreciated that sustaining exercise beyond a few seconds depends upon the appropriate supply and utilization of oxygen. However, the widespread use of incremental exercise tests on the one hand, and Douglas bag or mixing chamber analyses in which pulmonary gas exchange data are averaged over periods of 30 Á 60 s on the other, has led to the common misconceptions that: (1) following a ''lag'' in V O 2 at the onset of constant-load exercise (the ''oxygen deficit''), a steady state is always achieved within about 3 min; and (2) V O 2 increases linearly as power output increases to V O 2max .…”
Section: Oxygen Uptake Response To Exercise: Traditional Conceptsmentioning
confidence: 99%
“…[26], [27], [3], [4]) a new hyperbolicexponential discounting model has been derived. This hyperbolic-exponential discounting model makes use of the concept critical power which indicates the level of power that can be provided without increasing fatigue (e.g., [8], [11], [12], [15], [19], [26], [27]). Moreover, the assumption was made that the considered power spent is kept constant over time.…”
Section: Discussionmentioning
confidence: 99%